2018
DOI: 10.1371/journal.pone.0195060
|View full text |Cite
|
Sign up to set email alerts
|

Topographic effects on dispersal patterns of Phytophthora cinnamomi at a stand scale in a Spanish heathland

Abstract: Phytophthora cinnamomi is one of the most important plant pathogens in the world, causing root rot in more than a thousand plant species. This observational study was carried out on a P. cinnamomi infected heathland of Erica umbellata used as goat pasture. The patterns and shapes of disease foci and their distribution were described in a spatial and temporal context using an aerial photograph record. A set of topographic traits was selected on the basis of a disease dynamic hypothesis and their effects on obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…; Cardillo et al . ). Furthermore, the use of fungicide in PSF research can be an important experimental tool, especially in the field, as soil fungi arguably constitute one of the most important groups of soil‐borne pathogens (Raaijmakers et al .…”
Section: Methodsmentioning
confidence: 97%
“…; Cardillo et al . ). Furthermore, the use of fungicide in PSF research can be an important experimental tool, especially in the field, as soil fungi arguably constitute one of the most important groups of soil‐borne pathogens (Raaijmakers et al .…”
Section: Methodsmentioning
confidence: 97%
“…Previous studies have found that non-avian taxa could be associated with new outbreaks of Phytophthora spp. ; these included goats (Capra aegagrus hircus) (Cardillo, Acedo, & Abad, 2018), feral pigs (Sus scrofa) (Li, Williams, Fenwick, Hardy, & Adams, 2014) and slugs (Parke et al, 2008;Telfer et al, 2015), the latter two showing viable spores excreted after ingestion of infected material. could be achieved, and may lead to higher incidence of positive samples.…”
Section: Ta B L E 2 Number Of Birds Sampled Per Each Month Across Allmentioning
confidence: 99%
“…Remote sensing is a tool that can be used to monitor tree health in urban forests. It has been used to map Phytophthora and the distribution of the diseases they cause in different areas of the world [ 22 , 23 , 24 ]. Remotely sensed data acquired over four years, enabling changes in tree health to be determined, was utilized for our study.…”
Section: Introductionmentioning
confidence: 99%